Gold nanoparticle production by continuous-wave laser ablation in liquid media - Laura Carmona-Saldarriaga; Alex Ossa (Revista Facultad de Ingeniería Universidad de Antioquia)
Over the past two decades, gold nanoparticles have gained much attention because of their unique qualities, such as optical effects, catalytic response, high surface area, and low toxicity. Chemical synthesis and pulsed laser ablation are the primary methods to create these nanoparticles. However, pulsed laser ablation can be expensive because it requires specialized lasers. Using low-cost, continuous-wave lasers is suggested to create gold nanoparticles with diameters of approximately 100 nm. Two different gold target thicknesses were used to observe particle production at different irradiation times and pulse durations. Also, a simple approximation was used to estimate the on/off duration based on target thickness, which yielded good results. This technique can be implemented without incurring high costs, increasing the global ability to produce and use nanoparticles for various purposes.